Microstructure analysis of fiber-reinforced dense graded asphalt mixture incorporating polypropylene and polyethylene fibers - Rashida, Ferdaus (2024)
Addressing the persistent challenges of rutting and stripping in asphalt pavement, this study investigates the efficacy of incorporating polypropylene fiber (PPF) and polyethylene fiber (PEF) to asphalt mixtures, thereby offering a sustainable solution. The research compares the mechanism of asphalt binders reinforced with polymers against a control group with no fiber additives. Various dosages of PPF and PEF ranging from 0.5% to 2.5% by weight of the asphalt binder are examined. The physical properties including penetration, softening point, as well as mechanical properties such as Marshall stability, dynamic creep, and resilient modulus are evaluated. Microstructural analysis, utilizing techniques such as digital image analysis (DIP), scanning electron microscopy (SEM), and Fourier Transform Infrared (FTIR) spectroscopy, offers insights into the composition and structure of the modified asphalt binders. Furthermore, Morphological properties derived from image analysis are employed to quantify the cracking area in both modified and unmodified asphalt mixtures. The findings reveal that the inclusion of PPF and PEF significantly improves the rheological and mechanical properties of asphalt mixtures. Notably, 2% PPF and 2.5% PEF of asphalt mixtures is recommended for optimal enhancement. Moreover, this research introduces a novel application of digital image processing for crack detection, utilizing image analysis software. Overall, the study demonstrates substantial enhancements in asphalt properties through the incorporation of PPF and PEF, offering promising prospects for sustainable pavement materials.